Phase transfer catalysed reaction of potassium superoxide with some nitroalkanes in the presence of α,β-unsaturated enones - Singh K.N.; Raghuvanshi R.S.; Singh M. (My University, 2025)
Superoxide ion, generated in situ by the phase transfer reaction of potassium superoxide and 18-crown-6 ether, brings about an easy Michael addition of nitroalkanes to α,β-unsaturated enones to afford 1,4-addition products.